Analysis Of The Completeness Of Filling In Inpatient Medical Records In Putri Hijau Hospitals Medan - Kharina Rizki Aulia; Ermi Girsang; Sri Wahyuni Nasution (CV. Inara, 2022)
Basically the medical record is an important part of health care for patients in the hospital. Medical decisions taken by a doctor based on the diagnosis made will greatly affect the actions of patients in treatment. An accurate diagnosis is based on history, physical examination, supporting examination and written in the medical record file. The purpose of making a medical record to support the achievement of orderly administration in order to improve health services in the hospital. This study aims to analyze and determine the completeness of filling inpatient medical record files at the General Hospital Putri Hijau Medan . This type of research is descriptive with an approach Qualitative using the in-depth interview method from statements to six informants consisting of one pulmonary specialists, one nurse, three hospital management, chief medical records officer. The results of the study generally showed that from 40 medical record files by pulmonary specialists obtained the complete entry date (100%), the percentage of complete entry time (100%), the percentage of complete anamnese recording (80%) completed by the doctor, complete physical examination (55%), complete diagnosis as much as (95%), treatment and complete action as much as (100%), consent and complete action as much as (100%), clinical observations as complete as much as (67.5%), the return summary is completely filled (50%), and the doctor's name and signature are completely filled (90%). The incompleteness of filling medical records is due to doctors feeling the time is limited because of the large number of patients, lack of communication between doctors and nurses in completeness of completing record files, medical lack of monitoring conducted by the hospital. It is expected that doctors, nurses improve communication for the completeness of the medical record, the doctor as the person in charge of the medical record to be more concerned with completing the medical record. Hopefully the hospital management will be more assertive to provide sanctions to the doctor to be able to increase the completeness of the medical record and further enhance monitoring.